Aesthetic smile rehabilitation with ceramic laminates veneers: a clinical case (Research, Society and Development, 2020)
Introduction: Diastemas are spaces larger than 0.5mm between adjacent teeth and can cause aesthetic impairment of the smile. For treatment of diastemas one of options is the use of ceramic laminates veneers. Ceramics have a high aesthetic quality, color stability, mechanical resistance and clinical longevity. Objective: to report a clinical case of smile plastics for the treatment of diastemas using ceramic laminates veneers. Case report: the patient sought the dental service complaining about the spaces between the teeth. The proposed treatment was the making of ceramic laminates veneers. Initially, dental wear was performed, followed by the color selection of the dental substrate and molding of the teeth with vinyl polysiloxane impression materials. The mock-up was installed as provisional and the impression was sent to the prosthesis laboratory for making the lithium disilicate laminates veneers. After making the laminates, the dry and wet tests were performed and after the patient's approval, cementation was performed. On the teeth, prophylaxis was performed with pumice and water, followed by conditioning with phosphoric acid (37%, for 30 seconds) and application of the adhesive (without photopolymerizing). In the ceramic pieces, conditioning with hydrofluoric acid (10% for 20 seconds), phosphoric acid (37% for 1 minute), silane (until its evaporation) and adhesive (without light curing) was carried out. The laminates were then cemented with light-cured resin cement (light curing for 40 seconds). Conclusion: The use of ceramic laminates allowed the closure of diastemas and improved the harmony of the smile.